SISTEM INFORMASI PEMINJAMAN DAN PENGEMBALIAN BUKU PADA PERPUSTAKAAN FAKULTAS SYARIAH DAN HUKUM UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG - Emelia, Emelia (Jurnal Multidisipliner Bharasumba, 2023)
The library is a room that contains various collections of printed and non-printed materials that are useful for users, as a source for seeking information and knowledge. Several libraries have used computer technology to facilitate the work of officers in terms of inputting library data. The Library of the Faculty of Sharia and Law, Raden Fatah State Islamic University Palembang has also used computer technology in the process of recording information systems. Therefore, the Information System for Borrowing and Returning Books at the Library of the Faculty of Sharia and Law, Raden Fatah State Islamic University Palembang already uses Web-Based Slims. Web-based library information system, using the Slims program. Where the existence of an information system for borrowing and returning books at this library can help and facilitate the work of officers in making data reports for new books coming in, books borrowed, books that have been returned, and income for late fines for returning books. With computerized data collection, it produces more accurate reports without any errors.